1996
DOI: 10.1006/viro.1996.0526
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Caprine Arthritis Encephalitis VirusvifGene forin VivoReplication

Abstract: Replication of vif-caprine arthritis encephalitis virus (CAEV) is highly attenuated in primary goat synovial membrane cells and blood-derived macrophages compared to the wild-type (wt) virus. We investigated the requirement for CAEV Vif for in vivo replication and pathogenicity in goats by intra-articular injection of either infectious proviral DNA or viral supernatants. Wild-type CAEV DNA or virus inoculation induced persistent infection resulting in severe inflammatory arthritic lesions in the joints. We wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…However, Vif is dispensable for replication in other T-cell lines (permissive cells), such as CEM-SS (6,19,20,24,53,55,60,63,65,67). In vivo, Vif is essential for pathogenic infections of simian immunodeficiency virus (SIV) in rhesus macaques, caprine arthritis encephalitis virus in goats, and feline immunodeficiency virus in cats (16,28,29,34,35,43). Taken together, these observations suggest that vif plays a vital role in HIV-1 replication and pathogenesis in vivo.…”
mentioning
confidence: 96%
“…However, Vif is dispensable for replication in other T-cell lines (permissive cells), such as CEM-SS (6,19,20,24,53,55,60,63,65,67). In vivo, Vif is essential for pathogenic infections of simian immunodeficiency virus (SIV) in rhesus macaques, caprine arthritis encephalitis virus in goats, and feline immunodeficiency virus in cats (16,28,29,34,35,43). Taken together, these observations suggest that vif plays a vital role in HIV-1 replication and pathogenesis in vivo.…”
mentioning
confidence: 96%
“…The Vif protein, which modulates viral infectivity (8,11,13,15,19,27,32,40,45,53,56,57,(60)(61)(62) and pathogenicity (7,19,20,24,25,35), is present in nearly all lentiviruses, including human immunodeficiency virus type 1 (HIV-1). It is believed to act during the late stages of virus assembly by enabling the establishment of integrated provirus in new target cells.…”
mentioning
confidence: 99%
“…For example, Jurkat, CEM-SS, and SupT1 cells do not require Vif for HIV-1 replication (permissive cells); for H9 cells, CEM cells, and primary blood-derived monocytes, however, Vif is essential (nonpermissive cells). In the case of nonhuman lentiviruses, primary blood-derived monocytes derived from the appropriate animals fail to support the replication of Vif mutant viruses (10,19,45,61). Cell fusion experiments with permissive and nonpermissive cells have indicated that the nonpermissive phenotype is dominant (36,52), leading to the concept that there exist specific cellular factors that act as inhibitors of lentiviral replication and which Vif must overcome (36,52).…”
mentioning
confidence: 99%
“…For example, Jurkat and SupT1 cells do not require Vif for HIV-1 replication; for H9 cells and primary blood-derived monocytes (PBMCs), however, Vif is essential. In the case of nonhuman lentiviruses, PBMCs derived from the appropriate animals fail to support the replication of vif mutant viruses (14,33,42). This finding has led to the concept that specific cellular factors exist which act as inhibitors of lentiviral replication and which Vif must overcome (26,37).…”
mentioning
confidence: 99%